Computer task performance by subjects with Duchenne muscular dystrophy - Malheiros SR; Silva TD; Favero FM; Abreu LC; Fregni F; Ribeiro DC; de Mello Monteiro CB (Neuropsychiatric Disease and Treatment, 2015)
Silvia Regina Pinheiro Malheiros,1 Talita Dias da Silva,2 Francis Meire Favero,2 Luiz Carlos de Abreu,1 Felipe Fregni,3 Denise Cardoso Ribeiro,4 Carlos Bandeira de Mello Monteiro1,4,5 1School of Medicine of ABC, Santo Andre, Brazil; 2Department of Medicine, Paulista School of Medicine, Federal University of São Paulo, São Paulo, Brazil; 3Center for Neurosciences, University of São Paulo, São Paulo, Brazil; 4Post-graduate Program in Rehabilitation Sciences, Faculty of Medicine, University of São Paulo, São Paulo, Brazil; 5School of Arts, Sciences and Humanities, University of São Paulo, São Paulo, Brazil Aims: Two specific objectives were established to quantify computer task performance among people with Duchenne muscular dystrophy (DMD). First, we compared simple computational task performance between subjects with DMD and age-matched typically developing (TD) subjects. Second, we examined correlations between the ability of subjects with DMD to learn the computational task and their motor functionality, age, and initial task performance.Method: The study included 84 individuals (42 with DMD, mean age of 18±5.5 years, and 42 age-matched controls). They executed a computer maze task; all participants performed the acquisition (20 attempts) and retention (five attempts) phases, repeating the same maze. A different maze was used to verify transfer performance (five attempts). The Motor Function Measure Scale was applied, and the results were compared with maze task performance.Results: In the acquisition phase, a significant decrease was found in movement time (MT) between the first and last acquisition block, but only for the DMD group. For the DMD group, MT during transfer was shorter than during the first acquisition block, indicating improvement from the first acquisition block to transfer. In addition, the TD group showed shorter MT than the DMD group across the study.Conclusion: DMD participants improved their performance after practicing a computational task; however, the difference in MT was present in all attempts among DMD and control subjects. Computational task improvement was positively influenced by the initial performance of individuals with DMD. In turn, the initial performance was influenced by their distal functionality but not their age or overall functionality. Keywords: computer task, motor learning, Duchenne muscular dystrophy, movement time